(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Nutritional anaemia is frequently observed in India. Prevalence of anaemia in Indian children is 59% (Hb<11gm/dl) but it’s higher among rural children. Iron deficiency is most common type nutritional deficiency anaemia in children. The nearest correlation of iron deficiency anemia (IDA) can be made with Pandu Roga in Ayurveda. The side effects of oral allopathic iron preparations are very common, therefore to get a better alternative, two Ayurvedic medicines, the Guda Haritaki and Punarnava Mandura, were subjected to a clinical trial among children suffering from IDA. Aim: Determine the role of Guda Haritaki and Punarnava Mandura in the management of Pandu roga w.s.r. to iron deficiency anaemia among children. Materials and Methods: The study was conducted on 35 children of IDA for a period of 6 weeks. Clinical features (Panduta, Daurbalya etc.) and hematological parameters (Hb gm %, sr. ferritin etc.) were documented before, during and after treatment. Statistical Analysis Used: Observations of the study were analyzed and findings were evaluated by using statistical methods Results: In the present study 58.82% improvement in Panduta was observed with Guda haritaki, 65% with Punarnava Mandura and 67 % when both drugs were given together. No adverse effect of the trial drug was observed during the study. Conclusions: The results suggest that Punarnava mandura along with Guda Haritaki is more effective in comparison to single use of either formulation in the management of IDA in children.